VALUE RELEVANCE OF ACCOUNTING INFORMATION AND CORPORATE SOCIAL RESPONSIBILITY IN INDONESIA AND SINGAPORE - Narullia, Dwi; Subroto, Bambang (Universitas Brawijaya, Indonesia, 2018)
This study aims to examine the value relevance of accounting information and corporate social responsibility (CSR) for measuring the firm value of companies in Indonesia and Singapore. This study used secondary data in the form of financial statements, annual reports, CSR/ sustainability reports, as well as the company’s stock price data. 34 companies were taken as a sample in this study during period 2013–2015. The results show that earnings information was relevant for measuring firm value, both in Indonesia and Singapore. The book value of equity and operating cash flow information was considered relevant in Singapore companies, but in Indonesia, this information was not considered relevant for measuring firm value. CSR information was considered irrelevant in both countries.